Corrections to and comments on the publication dealing with the type specimens of Buprestidae (Coleoptera) deposited in NFIC, Dehradun, India - Bílý, Svatopluk (Zootaxa, 2018)
Corrections of the data given in the calalogue of types of the family Buprestidae deposited in the National Forest Insect Collection, Dehradun, India. Erroneously recorded nomina nuda, wrong status of type specimens, type depositions, authorships.